A Case of Primary Open-angle Glaucoma With Conjunctival Laceration After Micropulse Transscleral Cyclophotocoagulation. Issue 12 (December 2020) - Kiyama, Yu; Nakashima, Kei-Ichi; Inoue, Toshihiro
Abstract : Purpose: We report a case of primary open-angle glaucoma with conjunctival laceration after micropulse transscleral cyclophotocoagulation (MP-CPC). Patients and Methods: A 74-year-old man with primary open-angle glaucoma underwent MP-CPC using a Cyclo G6 device (IRIDEX) due to an increase in intraocular pressure (IOP) to 25 mm Hg in his left eye. At 1 week after surgery, IOP had decreased to 12 mm Hg. However, at 2 months after surgery, IOP had increased again to 25 mm Hg. MP-CPC was performed again at 3 months after the first surgery using a Cyclo G6 device, in accordance with treatment guidelines outlined by the manufacturer. Before the MP-CPC treatment, the patient received anesthesia with 2% lidocaine in the sub-Tenon space. A large amount of subconjunctival hemorrhage was observed in the sub-Tenon space. Results: At 1 day after the second MP-CPC treatment, an arc-shaped conjunctival erosion and a brown lesion were observed in the MP-CPC-irradiated area in the lower hemisphere. The possibility of scleral laceration was considered. The IOP was 25 mm Hg and no aqueous humor leakage was observed. The wound had become enlarged. At 20 days after the second MP-CPC, the patient was hospitalized to close the wound. During the repair surgery, the brown lesion was easily detached from the sclera. There was conjunctival laceration, but no scleral laceration. Pathologic examination revealed that the exfoliated tissue contained abundant clots, connective tissue, and elastic fibers. Conclusion: Special care and consideration are required when performing MP-CPC in cases of severe subconjunctival hemorrhage.